Implementasi Teori Behaviorisme dalam Pembentukan Karakter Disiplin Anak Usia Dini - Mujiburohman, Mujiburohman; Aziz, Nur; Al Faizi, Ahmad Akbar (TSAQOFAH, 2025)
Early childhood education is a critical phase in human development, serving to enhance children's potential and instill a sense of discipline that persists into adulthood. This study employs a library research methodology, utilizing books, journal articles, and other pertinent documents as data sources. Behaviorist theory posits that individual behavior results from learning processes that can be modified through appropriate learning environments and reinforcement of desired behaviors. Consequently, learning involves integrating existing knowledge with new information.